James Thwoat and Mary Batt deed - Thwoat, James; Batt, Mary.
Deed (Charles City County, Va.; 1700 June 1) transferring land of James Thwoat and Mary Batt to Matthew and Sarah Sturdivant.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Sturdivant, Matthew; Sturdivant, Sarah; Deeds -- Virginia -- Charles City County; Land tenure -- Virginia -- Charles City County